Evaluation of Anaphylaxis Management in a Pediatric Emergency Department. Issue 8 (August 2016) - Sidhu, Natasha; Jones, Stacie; Perry, Tamara; Thompson, Tonya; Storm, Elizabeth; Melguizo Castro, Maria S.; Nick, Todd G.
Abstract : Objective: In 2006, the National Institute of Allergy and Infectious Disease established evidence-based treatment guidelines for anaphylaxis. The purpose of our study was to evaluate provider adherence to guidelines-based management for anaphylaxis in a tertiary care pediatric emergency department (ED). Methods: Retrospective chart review was conducted of patients (0–18 years) presenting to the Arkansas Children Hospital ED from 2004 to 2011 for the treatment of anaphylaxis using International Classification of Diseases, Ninth Edition, codes. Multiple characteristics including demographics, clinical features, allergen source, and anaphylaxis management were collected. Fisher exact or χ 2 tests were used to compare proportion of patients treated with intramuscular (IM) epinephrine in the preguideline versus postguideline period. Relative risk (RR) statistics were computed to estimate the ratio of patients who received self-injectable epinephrine prescription and allergy follow-up in the preguideline and postguideline groups. Results: A total of 187 patients (median [range] age, 7 [1–18] years; 67% male; 48% African American) were evaluated. Food (44%) and hymenoptera stings (22%) were commonly described culprit allergens, whereas 29% had no identifiable allergen. Only 47% (n = 87) received epinephrine in the ED and 31% (n = 27) via the preferred IM route. Comparing postguideline (n = 126) versus preguideline (n = 61) periods demonstrated increase in the usage of the IM route (46% postguideline vs 6% preguideline; risk ratio (RR), 7.64; 95% confidence interval [CI], 2.04–46.0; P < 0.001). Overall, 61% (n = 115) of the patients received self-injectable epinephrine upon discharge, and there were no significant differences between the groups (64% postguideline vs 56% preguideline, P = 0.30). Postguideline patients were more likely to receive a prescription compared with preguideline patients (64% postguideline vs 56% preguideline; RR, 1.15; 95% CI, 0.89–1.55; P = 0.30). Only 45% (n = 85) received an allergy referral. Postguideline patients were more likely to receive an allergy referral than preguideline patients (48% postguideline vs 41% preguideline; RR, 1.16; 95% CI, 0.81–1.73; P = 0.40). Conclusions: Provider use of IM epinephrine has improved since anaphylaxis guidelines were published. However, more provider education is needed to improve overall adherence of guidelines in a tertiary care pediatric ED.